Research on the Path of Digital Enabling New Quality Productivity in Yangtze River Delta - Xiao, Yishan; Wan, Yuting; Wang, Na; Zhou, Xueting; Wang, Xianmei (International Journal of Social Sciences and Public Administration, 2024)
As one of the most economically developed regions in China, the Yangtze River Delta (YRD) region has always been in the leading position in the country in terms of economic development. However, with the changes in the global economic situation and the promotion of scientific and technological innovation, the Yangtze River Delta region is also facing new development challenges and opportunities. Digital empowerment, as an important driving force of the new round of technological revolution, is of great significance to the development of new quality productivity in the Yangtze River Delta region. As new quality productivity has become the buzzword of China's economic development, how can the Yangtze River Delta recognize the timing and take the pulse of development? Therefore, this study aims to deeply explore the path of digitally-enabled new quality productivity in the Yangtze River Delta region, and provide theoretical and practical support for the sustainable development of the regional economy. By analyzing the impact of digital empowerment on new-quality productivity in the Yangtze River Delta region, this study intends to explore the mechanism of the role of digital empowerment in enhancing new-quality productivity and propose corresponding paths and strategies. Specific research questions include: what is the current status of digital empowerment in the Yangtze River Delta region? What is the impact mechanism of digital empowerment on new quality productivity? How should the path of digital empowerment of new quality productivity in the Yangtze River Delta region be constructed?